Gearing tax policy and tax administration for the year 2000 - Yoingco, Angel Q. (1994)
Tax revenue growth in the Philippines has been stymied by structural, organizational and behavioral problems, for example, incoherent and complicated tax structure, inefficient tax collection, graft and corruption, poor tax compliance, and others. To support the attainment of an economically developed Philippines in the year 2000, the author proposes putting in place a broad but simple and efficient tax system that features the following reforms: simplification of tax structure, systematization of operational procedures, and cleansing of the administrative machinery to imbue it with a high level of competence, integrity and morale.
Keywords: Tax policy; Tax administration and procedure